2022
DOI: 10.1186/s42523-022-00198-5
|View full text |Cite
|
Sign up to set email alerts
|

A framework for testing the impact of co-infections on host gut microbiomes

Abstract: Parasitic infections disturb gut microbial communities beyond their natural range of variation, possibly leading to dysbiosis. Yet it remains underappreciated that most infections are accompanied by one or more co-infections and their collective impact is largely unexplored. Here we developed a framework illustrating changes to the host gut microbiome following single infections, and build on it by describing the neutral, synergistic or antagonistic impacts on microbial α- and ß-diversity expected from co-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 108 publications
1
11
0
Order By: Relevance
“…While we lack detailed information on pathogen communities in wild meerkats, nematode infections are present in our study population (Smyth & Drea, 2016) and thus might contribute to variation in TB progression in this species. Moreover, climate change and environmental or social disturbances can drive co‐infections and might even facilitate the emergence of novel pathogens or the re‐emergence of endemic, but historically unproblematic pathogens via shifts in host‐associated gut microbiota (Risely et al., 2022; Schmid et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While we lack detailed information on pathogen communities in wild meerkats, nematode infections are present in our study population (Smyth & Drea, 2016) and thus might contribute to variation in TB progression in this species. Moreover, climate change and environmental or social disturbances can drive co‐infections and might even facilitate the emergence of novel pathogens or the re‐emergence of endemic, but historically unproblematic pathogens via shifts in host‐associated gut microbiota (Risely et al., 2022; Schmid et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While multiple studies have indicated that pathogens can affect the gut microbiota of their wildlife host (Aivelo & Norberg, 2018; Wasimuddin et al, 2019), very few of these have considered possible effects of coinfection (Sabey et al, 2021; Schmid et al, 2022). Yet, coinfections are ubiquitous in wildlife (Hoarau et al, 2020), and indeed nearly 19% of voles in our study were coinfected (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Ap‐N, Ap‐S and Ap‐C), irrespective of the specific coinfections (Table S1). Furthermore, we used a framework proposed by Schmid et al (2022) to compare the effects of coinfections on gut microbiota with those of a single infection. The framework defines ‘synergistic’ effects of coinfection as those that exacerbate changes in the gut microbiota.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations